Social Sciences Teaching in the Face of the Global Challenges of the 21st Century - Morote, Álvaro-Francisco (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
At present, the world is experiencing global changes that have effects on all social, economic, political, and environmental fields, etc. Climate change, natural hazards, social inequalities, immigration, refugees, and the spread of diseases (COVID-19, etc.) are just some examples of topics addressed by Social Sciences. All of these questions can be dealt with in the field of education at all educational stages (including university). We now are now facing different problems that must be dealt with in Social Sciences classes (mainly those of Geography and History), and that can be linked to the so-called Sustainable Development Goals (SDGs): "gender equality" (SDG 4), "clean water and sanitation" (SDG 5), "affordable and clean energy" (SDG 6), "reduction of inequalities" (SDG 10), "sustainable cities and communities" (SDG 11), "responsible production and consumption" (SDG 12), "climate action" (SDG 13), "life of terrestrial ecosystems" (SDG 15) and "peace, justice and strong institutions" (SDG 16). This Special Issue aims to answer the following research questions through theoretical and empirical studies: *What are the purposes of teaching History, Geography and Social Sciences in schools today? *What place do social thought formation and social problems have in learning/teaching in Social Sciences?